Characterization of rpoB Mutations in Rifampin-Resistant Clinical Isolates of Mycobacterium tuberculosis from Turkey by DNA Sequencing and Line Probe Assay - Cavusoglu, Cengiz (American Society for Microbiology (ASM), 2002)
Mutations in an 81-bp region of the rpoB gene associated with rifampin resistance were studied in 41 rifampin-resistant clinical strains of Mycobacterium tuberculosis isolated in Turkey. Fourteen different rpoB alleles, three of which had not been reported before, were found. A reverse hybridization-based line probe assay (the Inno-LiPA Rif.TB test) for rapid detection of the mutations was evaluated with these isolates. Rifampin resistance was correctly identified in 23 of 41 isolates (56.1%) with the kit's R probes specific for these mutations. Seventeen of 41 isolates (41.5%) yielded hybridization patterns, with at least one negative signal obtained with the S probes for the wild type. One isolate was identified as rifampin sensitive by the line probe assay. The rate of concordance of the results of the line probe assay with the results of the in vitro susceptibility test was high (97.6%). These results demonstrate that the line probe assay kit may be useful for the rapid diagnosis of rifampin-resistant tuberculosis.